Deficient or R273H and R248W Mutations of p53 Promote Chemoresistance to 5-FU via TCF21/CD44 Axis-Mediated Enhanced Stemness in Colorectal Carcinoma - Gao, Xiaolei; Zheng, Xuan; Zhang, Yixin; Dong, Liying; Sun, Liangjie; Zhao, Na; Ding, Chong; Ma, Zeyun; Wang, Yixiang (Frontiers in Cell and Developmental Biology, 2022)
Background: p53 mutations are highly frequent in various human cancers and are reported to contribute to tumor malignance and chemoresistance. In this study, we explored the mechanism by which mutant p53 promotes carcinogenesis and chemoresistance and provided novel insights into cancer therapy. Materials and methods: A total of 409 patients with colorectal carcinoma from TCGA database were subdivided into two groups according to the p53 status, namely, mutant p53 and wild-type p53, following with GSEA analysis. The differences of the clinicopathologic index were also analyzed. Two HCT116 cell lines containing hot spots at codons R273H and R248W of p53 were constructed based on HCT116 with knockout p53, respectively. Cell viability, mobility, clonogenesis, and stemness were detected by CCK8, transwell migration and invasion, colonogenic, and sphere formation assays. Resistance to 5-FU was examined by live-dead staining and flow cytometry. qPCR, Western blot, and luciferase reporter assay were performed to identify that deficient or mutant p53 promoted chemoresistance of the colorectal carcinoma cell line HCT116 through the TCF21/CD44 signaling pathway, with the following rescue assays by overexpression of TCF21 and knockdown of CD44. Results: Patients with recurrence harbor a higher frequency of mutant p53 than those without recurrence (p < 0.05). The mutant p53 group developed a larger tumor than the wild-type one. GSEA analysis showed that oncogenic signatures were enriched in the mutant p53 group. Extracellular assays showed that cancer cells with deficient or mutant p53 (R273H and R248W, respectively) promoted colon cancer cell growth, migration, invasion, and stemness. The mutant cancer cells were also observed to be significantly resistant to 5-FU. Xenografts also confirmed that HCT116 cells harboring deficient or mutant p53 promoted cancer growth and 5-FU tolerance. Luciferase reporter assay showed that deficient or mutant p53 R237H and R248W endowed cancer cells with chemoresistance by activating CD44 via repressing the nuclear transcription factor TCF21 expression. Overexpression of TCF21 or knockdown of CD44 could rescue the sensitivity to 5-FU in deficient and mutant p53 HCT116 cell lines. Conclusion: Our results, for the first time, reveal a novel deficient or mutant p53/TCF21/CD44 signaling pathway which promotes chemoresistance in colorectal carcinoma. The axis could be an effective therapeutic strategy against deficient- or mutant p53-driven chemoresistance.